Rheology and microstructural studies of regenerated silk fibroin solutions - Nisal, Anuya; Kalelkar, Chirag; Bellare, Jayesh R.; Lele, Ashish K. (Rheologica Acta, 2013)
Regenerated silk fibroin solutions (RSF) are produced by dissolving degummed silk fibers in water. We have observed that RSF solutions at a concentration less than 15 % by weight exhibit an unusual gel-like response in conventional shear rheology measurements. At higher concentrations, the response is predominantly viscous (or liquid-like). We have probed this counterintuitive behavior of silk fibroin solutions by using microrheology, and interfacial rheometry. Scattering techniques were also used to understand the microstructure of RSF solutions as a function of the concentration. Our studies suggest that the gel-like response of the RSF solution may result from the formation of an interfacial film at the air-solution interface, which dominates the bulk rheological response.
Keywords: Interfacial rheology; Microrheology; Rheology; Silk